2015
DOI: 10.5433/1679-0359.2015v36n4p2545
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of replacing wheat flour with chia flour (Salvia hispanica L.) in pasta

Abstract: In recent years, chia (Salvia hispanica L.) has become increasingly more prevalent in the Brazilian diet and has triggered the interests of many researchers due to its functional properties and associated health benefits. The objective of this study was to develop pasta with different percentages of chia flour in lieu of wheat flour, and to evaluate the impact of chia on the nutritional, technological, and sensory properties of pasta. Pastas were prepared by replacing 7.5% (T1), 15% (T2), and 30% (T3) of wheat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
22
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 12 publications
3
22
0
Order By: Relevance
“…However, in the case of replacement of 50–75% oil in dough, an adverse change was observed in density and overall quality of the baked product [69]. As shown by Oliveira et al [70], flour from chia seeds may also be used to produce pasta as a substitute of wheat flour. In that experiment, they found that pasta prepared with a share of chia flour had a greater nutritive value than the control pasta.…”
Section: Application Of Chia Seeds In Food Industrymentioning
confidence: 99%
See 1 more Smart Citation
“…However, in the case of replacement of 50–75% oil in dough, an adverse change was observed in density and overall quality of the baked product [69]. As shown by Oliveira et al [70], flour from chia seeds may also be used to produce pasta as a substitute of wheat flour. In that experiment, they found that pasta prepared with a share of chia flour had a greater nutritive value than the control pasta.…”
Section: Application Of Chia Seeds In Food Industrymentioning
confidence: 99%
“…It had statistically significantly greater contents of protein, minerals and dietary fibre. It was recorded that pasta with 7.5% wheat flour replaced with chia flour exhibited very good technological properties and received the highest acceptance index in terms of taste [70]. Menga et al [42] proposed adding chia seeds and mucilage to rice flour for gluten-free fresh pasta.…”
Section: Application Of Chia Seeds In Food Industrymentioning
confidence: 99%
“…The chia seed approval as a Novel Food by the European Parliament has led to a high degree of usage of chia seed in a wide range of foods at levels up to 10% [ 8 , 9 , 10 ]. There are several studies on the influence of chia on various food products, such as pasta [ 11 ], biscuits [ 12 ] and bread [ 13 , 14 , 15 , 16 , 17 ]. Recently, the use of two partially defatted powders of chia enriched with proteins or fibres was authorized as food supplements for the adult population, or as nutritional ingredients in a variety of foods [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Mohd Ali et al [2012] concluded that chia oil can maintain a balanced serum lipid profile, while Citelli et al [2016] observed changes in the lipid profile in the liver caused by chia oil supplementation. Chia inter alia has been used for the production of bread [Coelho & Salas-Mellado, 2015; Hrušková & Švec, 2015; Miranda-Ramos et al, 2020; Romankiewicz et al, 2017], pasta [Oliveira et al, 2015], and even ice cream [Campos et al, 2016]. Several studies of bread with chia seeds showed that they contributed to the technological quality and texture parameters, depending on additive type -flour or seeds, and the method of their preparation.…”
Section: Introductionmentioning
confidence: 99%